Review of the South African and Mozambican stomatopod fauna - Brokensha, Rouane (Department of Biological Sciences, 2023)
Mantis shrimps or stomatopods (Crustacea: Stomatopoda) form an important component of the marine benthos and are notorious predators. Globally some 480 species have been described. However, the current taxonomic knowledge on the mantis shrimp fauna of southern Africa remains limited and outdated, with the last taxonomic revision of the group being that of K.H. Barnard in 1950, who recorded 17 species from South Africa and southern Mozambique. The present study aims to collate literature records, examine existing museum specimens, update species accounts and distribution records, and report on new species records from both South Africa and Mozambique. This study is primary based on the stomatopod collection housed at the Iziko South African Museum, Cape Town, South Africa. A guide to the South African stomatopod fauna is presented in Chapter 1. Keys for South African superfamilies, families, genera and species are compiled to produce the first comprehensive and fully illustrated identification guide to the mantis shrimps of South Africa. Detailed taxonomic accounts of all known species are given, and drawn illustrations presented for those species for which material was available, which includes new feature variations for species and genera worldwide, as well as in South Africa. Five species are added as new records for the region, increasing the number of South African stomatopods from 26 to 31 species belonging to 20 genera from nine families. Lysiosquilla colemani is recorded for the second time globally as a new record for the Western Indian Ocean and South Africa. Another little-known species, Gonodactyllelus crosnieri, is also recorded for the second time and represents a new species record for South Africa. Furthermore, genus Odontodactylus comprised of two species, O. hansenii and O. scyllarus, is taxonomically presented from South African material for the first time. The second species of Clorida from South Africa, C. albolitura is also recognised as a new record for southern Africa. Chapter 2 reports on notable stomatopods from Mozambique present in the material housed in the Iziko South African Museum. Seven species are recorded for the first time from Mozambican waters, bringing the known Mozambican stomatopod fauna to 22 species in 17 genera and eight families. Taxonomic accounts of eight species are given, seven of these representing new species records, while the eighth description is of the previously poorly documented species, Erugosquilla woodmasoni, which is reported on from new material. The new record of Manningia australiensis represents the first record of the family Eurysquillidae from southern Africa. While this study examines existing collections of southern African stomatopods, it was not possible to sample additional fresh material and the stomatopod fauna of southern Africa, and especially Mozambique, remains highly under-sampled. The present guide and species additions provide a detailed account of the fauna, thereby improving our current understanding of this distinctive group in this unique geographic area. Using this guide and the collated information therein, future taxonomic work will be well-equipped to take advantage of modern techniques when collecting new material from previously under-sampled habitats.